ANALISIS SOAL UJIAN SEMESTER II IPA/BIOLOGI KELAS VIII MTsN KOTA SOLOK TAHUN PELAJARAN 2012/2013 - Nelfita, Silvia - (STKIP PGRI Sumbar, 2014)
Items analysis is an activity that can help to increase the learning result test. There are some problems occur, i.e. a difficult item test, the students are difficult to understand the item test, and the item test has not been tested yet. The test result of IPA/Biology for the second semester is classified into low and it is under the Minimum Accomplished Criteria (KKM), i.e. 70. The research aims to give information about the semester test items of VIII class IPA/Biology test of second semester of MTsN Solok city in academic year 2012/2013. The research is a descriptive research, in which the researcher describes and interprets the data as it is. The result of item validity data is for the high criteria i.e. 3 items (6%), moderate criteria i.e. 12 items (24%), low criteria i.e. 18 items (36 %), and very low i.e. 17 items (34%). Based on the good item validity criteria, there are only 15 items (30%) valid. The item reliability is 0.79 included the high criteria, the index of item difficulty for difficult criteria i.e. 25 items (50%), moderate criteria, i.e. 18 items (36%), and easy criteria, i.e. 7 items (14%). The distinguisher items is for worse criteria, i.e. 22 items (44%), moderate criteria i.e. 17 items (34%), good criteria, i.e. 7 items (14%) and bad criteria, i.e. 4 items (8%). The option effectivities are 31 effective key options (62%), 19 uneffective options (38%). The distractor options are 33 effective (66 %) and 17 uneffective (34%).